Joint Beamforming, Scheduling, Trajectory, and Transmit Power Optimization in UAV-Assisted ISAC Systems for Information Freshness - Yuting He; Qingjie Wu; Miao Cui; Yuan Peng; Guangchi Zhang; Wei Chen (IEEE Access)
In this paper, we consider a system that integrates an unmanned aerial vehicle (UAV) for sensing and communication. The UAV is responsible for communication with multiple users and sensing targets for multiple users. Our objective is to minimize the age of information (AoI) of the sensory data by jointly optimizing the scheduling, transmit beamforming, trajectory, and transmit power of the UAV, while considering the communication quality constraints and physical constraints. To solve the optimization problem in a low-complexity manner, we first derive a closed-form solution for the transmit beamforming. Then, we decompose the remaining problem into two subproblems: one focuses on maximizing the total amount of the target sensing time, while the other aims to minimize the total amount of the sensing task completion time. For the former subproblem, we propose a low-complexity chain-based algorithm. For the latter subproblem, we utilize the Lagrange dual method and successive convex approximation technique. Simulation results show that our proposed algorithm can achieve a smaller average AoI with a low complexity compared to benchmark schemes.